Effects of whole-body vibration training in a cachectic C26 mouse model - Miranda van der Ende (Nature Portfolio, 2021)
Abstract Targeted exercise combined with nutritional and pharmacological strategies is commonly considered to be the most optimal strategy to reduce the development and progression of cachexia. For COPD patients, this multi-targeted treatment has shown beneficial effects. However, in many, physical activity is seriously hampered by frailty and fatigue. In the present study, effects of whole-body-vibration-training (WBV) were investigated, as potential alternative to active exercise, on body mass, muscle mass and function in tumour bearing mice. Twenty-four male CD2F1-mice (6–8 weeks, 21.5 ± 0.2 g) were stratified into four groups: control, control + WBV, C26 tumour-bearing, and C26 tumour-bearing + WBV. From day 1, whole-body-vibration was daily performed for 19 days (15 min, 45 Hz, 1.0 g acceleration). General outcome measures included body mass and composition, daily activity, blood analysis, assessments of muscle histology, function, and whole genome gene expression in m. soleus (SOL), m. extensor digitorum longus (EDL), and heart. Body mass, lean and fat mass and EDL mass were all lower in tumour bearing mice compared to controls. Except from improved contractility in SOL, no effects of vibration training were found on cachexia related general outcomes in control or tumour groups, as PCA analysis did not result in a distinction between corresponding groups. However, analysis of transcriptome data clearly revealed a distinction between tumour and trained tumour groups. WBV reduced the tumour-related effects on muscle gene expression in EDL, SOL and heart. Gene Set Enrichment Analysis showed that these effects were associated with attenuation of the upregulation of the proteasome pathway in SOL. These data suggest that WBV had minor effects on cachexia related general outcomes in the present experimental set-up, while muscle transcriptome showed changes associated with positive effects. This calls for follow-up studies applying longer treatment periods of WBV as component of a multiple-target intervention.